A closer look into the materialism construct: the antecedents and consequences of materialism and its three facets. Issue 2 (16th March 2015) - Segev, Sigal; Shoham, Aviv; Gavish, Yossi
Abstract : Purpose: – This study aims to unbundle the materialism construct into its three facets – centrality, success and happiness – to provide a fine-grained model that delineates the relationship between some of its antecedents (i.e. depression, anxiety, self esteem and affect) and consequences (life satisfaction, innovativeness, time spent shopping and environmentalism). Design/methodology/approach: – Using a convenience sample of 568 adult consumers, this study tests a model in which a set of psychological variables serve as antecedents of materialism and its three facets, which in turn affect a set of cognitive, psychological and behavioral consequences. Findings: – Results indicate that specific facets have more weight than others, depending on the nature of the needs individuals seek to fulfill through possessions, or their resulting behaviors and cognitions. Results validate the view of materialism as a coping mechanism, but also show that the consequences of materialism can be both positive and negative depending on their underlying facet. Research limitations/implications: – This study used a convenience sample, which might affect the generalizability of its findings. The materialism centrality subscale showed a lower than desirable level of reliability. Future research might consider using the longer, 6-item version of this sub-scale. Practical implications: – This study helps marketers identify the circumstances under which materialism can lead to negative or positive consequences. Marketers should be careful when designing messages that make unrealistically strong associations between consumption and happiness, positive emotions, self-worth and satisfaction with life. Social implications: – The negative social and personal consequences of materialism call for the formulation of policies designed to reduce them, and marketers' responsibility to consumers' well-being, especially among potentially vulnerable segments of the population. Originality/value: – This study provides an in-depth analysis of the materialism construct, its antecedents and outcomes. It advances our understanding of how materialism works by examining each facet separately and how it is related to the various psychological antecedents and consumer behavior outcomes.